The Gap Between Tools and Best Practice: An Analysis of Safety Prequalification Surveys in the Construction Industry. (February 2019) - Liu, Kang-Hung; Tessler, Jamie; Murphy, Lauren A.; Chang, Chien-Chi; Dennerlein, Jack T.
This study characterizes safety prequalification surveys currently in use in the construction industry to identify approaches that include leading indicators of worker safety performance. We collected prequalification surveys available in the public domain from internet searches, construction company websites, published literature, and construction industry partners. We utilized a conceptual framework, based on safety theory and best practices, to categorize survey questions. Fifty-two prequalification surveys were identified containing 112 unique questions. Most included questions related to lagging indicators (83 percent), safety management leadership (75 percent), and worker training (60 percent). Safety management system elements such as hazard prevention and control, program evaluation and improvement, and coordination and communication were notably absent in 90 percent of the surveys. There was little consistency in the surveys available concerning leading indicators of safety. Only a small number of surveys currently in use incorporate all the elements of best practices associated with robust safety management systems.